Cascaded navigation control for agricultural vehicles tracking straight paths - Jingtao, Hu; Taochang, Li (International Journal of Agricultural and Biological Engineering, 2014)
In precision agriculture (PA), an agricultural vehicle navigation system is essential and the navigation control accuracy is important in this system. As straight path tracking is the major operating mode of agricultural vehicles on large fields, a cascaded navigation control method for straight path tracking is proposed in this study. Firstly, a cascaded navigation control structure for the agricultural vehicle was discussed. Based on this structure, the navigation control task was decomposed into two cascaded control tasks, namely, the path tracking control task and the steering control task. Secondly, a relative kinematics model of agricultural vehicles was deduced, and an optimal Proportional-Derivative (PD) method based on the deduced model was developed in the path tracking control task. Then, an improved PD method based on a transition process was proposed in the steering control task to enhance the performance of the steering control subsystem. Finally, the effectiveness and the superiority of the proposed method were verified by a series of experiments. Results of the experimental data analysis show that mean value of the lateral position deviation is 0.02 m and standard deviation of the lateral position deviation is 0.04 m, which proves that the proposed method has achieved satisfactory effects on the straight path tracking of agricultural vehicles.